Primulina fengkaiensis (Gesneriaceae), a new species from limestone areas in Western Guangdong, China - Lin, Ning Zu; Bo, Pan; Ming, Kang (Phytotaxa, 2015)
Primulina fengkaiensis from western Guangdong, China, is described and illustrated. It is similar to the phylogenetically related P. baishouensis and P. gueilinensis in the shape and size of corolla, but differs by leaf blades being elliptic to elliptic–lanceolate, 10–21 × 4–8 cm, margin with serrate, leaf blade adaxially sparsely pubescent, petiole 0.6–1.5 cm wide, pedicel 2.2–4 (–7.5) cm long, cymes 3–9–flowered, stigma 4–5 mm long, lobes ovate.